Moral and philosophical problems in the novel "Crime and Punishment" by Fyodor Dostoevsky - Abdukhalilova , Nozimakhon (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article analyzes the main moral and philosophical ideas of the novel “Crime and Punishment”, revealing the inner conflict of the protagonist and the importance of spiritual rebirth.